Technologies and Research Trends in Wireless Body Area Networks for Healthcare: A Systematic Literature Review - Ilkyu Ha (International Journal of Distributed Sensor Networks)
Owing to the increasing interest in the integration of the medical technology and the information and communications technology, research on wireless body area networks (WBANs), which apply a sensor network to the human body, is being actively conducted. Existing sensor network technology has the potential to be used in a WBAN; however, it has some limitations. In particular, a WBAN has a very different network environment compared to a sensor network that uses free space, because wireless sensors in a BAN transmit through parts of the human body. Therefore, research on WBANs involves a variety of research areas that differ slightly from those of conventional sensor networks and take into account the characteristics of the human body. This study investigates the environmental characteristics of a WBAN that differ from conventional sensor networks and examines the areas that have been studied in academia to realize more efficient WBANs. From studies published since 2001, when the concept of the WBAN was introduced, research trends in WBANs were investigated using the systematic literature review (SLR) technique. The investigation in this study includes the classification of research and research fields in line with research content. Further, survey results are presented and the outlook for further study is summarized.